Evaluation of Informatization Performance of Construction Industrialization EPC Enterprises in China - Fuyi Yao; Yingbo Ji; Hong Xian Li; Guiwen Liu; Wenjing Tong; Yan Liu; Xiaowei Wang (Advances in Civil Engineering)
An enormous amount of investment has been spent towards informatization for the construction industrialization engineering, procurement, and construction (EPC) enterprises in China; however, the performance output remains uncertain. This paper aims to evaluate the informatization performance of the construction industrialization enterprises in China based on a proposed evaluation framework. The proposed framework entails a hierarchical input and output structure; the input metrics include 4 first-level and 17 second-level indicators, and the outputs include 6 first-level and 27 second-level indicators as the metrics, respectively. Survey and interview are utilized to collect data, with effective responses from thirty construction industrialization EPC enterprises. The informatization performance of these enterprises is evaluated using an improved D-FCA method, which incorporates the analytic hierarchy process (AHP), data envelopment analysis (DEA), and fuzzy comprehensive evaluation analysis (FCA). The research results indicate that all the surveyed enterprises meet the performance requirement, and 60% of the thirty enterprises show excellent performance, reaching A level, AA level, and AAA level. Furthermore, for those enterprises with DEA scores less than 1, which indicates inefficient use of the resources during the informatization process, strategies are proposed to improve the performance of these enterprises. This study contributes a comprehensive framework to evaluate the informatization performance of construction industrialization enterprises in China. The enterprises studied currently mainly come from some developed areas, and the overall situation for construction industrialization needs to be further studied in future research.